If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(5x) + -1sin(3x) = cos(4x) Remove parenthesis around (5x) ins * 5x + -1sin(3x) = cos(4x) Reorder the terms for easier multiplication: 5ins * x + -1sin(3x) = cos(4x) Multiply ins * x 5insx + -1sin(3x) = cos(4x) Remove parenthesis around (3x) 5insx + -1ins * 3x = cos(4x) Reorder the terms for easier multiplication: 5insx + -1 * 3ins * x = cos(4x) Multiply -1 * 3 5insx + -3ins * x = cos(4x) Multiply ins * x 5insx + -3insx = cos(4x) Combine like terms: 5insx + -3insx = 2insx 2insx = cos(4x) Remove parenthesis around (4x) 2insx = cos * 4x Reorder the terms for easier multiplication: 2insx = 4cos * x Multiply cos * x 2insx = 4cosx Solving 2insx = 4cosx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Divide each side by '2nsx'. i = 2cn-1o Simplifying i = 2cn-1o
| -64x^2+16=0 | | n^2+9n+28=0 | | 0.4*7/3*8/15 | | n+9n+28=0 | | 0.4*7/3 | | 8x-4=4x+16 | | (27m^5-16m^2)/3m | | 6u+42=-3(u+7) | | 2/6x4 | | 7p+9=-9(p-3) | | x=3929.25-3665 | | 2x+2=2(2-x)+6 | | 2.75x+35=2.45x+95 | | 0.0977=ln(x) | | (x+6)(2x-5)+(x+6)(x+9)=0 | | 3.35x=2.75x+35 | | 10x-4+2x=-24 | | -x^2+2x+4= | | 5a+4b=10 | | 16=6x+x^2 | | 3(2n+1)=9 | | 0=y^2+5y-36 | | 84=x/6 | | 11=6+1.2(x-6) | | ((X^-1/2)(x^5/2))/(x^1/3) | | U=2(9n+35)+7(n+1) | | ((8b^5c^2)/(15c))x(3c/2b) | | -34+u=-16 | | 5=1.2(x-7) | | cot^2(x)=1 | | (9a^2b^(-3/2))^(1/2) | | 13/y/=3/8 |